Analyzing General Anti-Avoidance Rule (GAAR) Policy in Indonesia (E-Jurnal Akuntansi, 2026)
The General Anti-Avoidance Rule (GAAR) provision, rooted in the substance over form principle, has been codified in the HPP Law and Government Regulation No. 55/2022. Much of the prior research on GAAR was conducted before the enactment of these regulations. To address this gap, the present study aims to assess the legal certainty of Indonesia's GAAR as it pertains to the substance over form principle and offers recommendations for improving the law in this area. This study adopts a qualitative research methodology, utilizing a case study approach that includes a review of relevant literature and interviews with regulators and stakeholders. The findings reveal that the GAAR provision outlines three specific conditions under which it can be applied. However, the provision does not explicitly state that obtaining a tax benefit must be the primary purpose of the transaction, leaving some ambiguity. To enhance the clarity and effectiveness of the GAAR, the implementing guidelines should emphasize this clause and provide clear definitions for "transaction," "tax benefit," and the "purpose test." Whether these terms are interpreted broadly or narrowly should align with the intended scope of Indonesia's GAAR.
Keywords: Tax Avoidance; General Anti-Avoidance Rule; Substance Over Form Principle